A circuit for secretion‐coupled cellular autonomy in multicellular eukaryotic cells. Issue 4 (1st March 2023) - Qiao, Lingxia; Sinha, Saptarshi; Abd El‐Hafeez, Amer Ali; Lo, I‐Chung; Midde, Krishna K; Ngo, Tony; Aznar, Nicolas; Lopez‐Sanchez, Inmaculada; Gupta, Vijay; Farquhar, Marilyn G; Rangamani, Padmini; Ghosh, Pradipta
Abstract: Cancers represent complex autonomous systems, displaying self‐sufficiency in growth signaling. Autonomous growth is fueled by a cancer cell's ability to "secrete‐and‐sense" growth factors (GFs): a poorly understood phenomenon. Using an integrated computational and experimental approach, here we dissect the impact of a feedback‐coupled GTPase circuit within the secretory pathway that imparts secretion‐coupled autonomy. The circuit is assembled when the Ras‐superfamily monomeric GTPase Arf1, and the heterotrimeric GTPase Giαβγ and their corresponding GAPs and GEFs are coupled by GIV/Girdin, a protein that is known to fuel aggressive traits in diverse cancers. One forward and two key negative feedback loops within the circuit create closed‐loop control, allow the two GTPases to coregulate each other, and convert the expected switch‐like behavior of Arf1‐dependent secretion into an unexpected dose–response alignment behavior of sensing and secretion. Such behavior translates into cell survival that is self‐sustained by stimulus‐proportionate secretion. Proteomic studies and protein–protein interaction network analyses pinpoint GFs (e.g., the epidermal GF) as key stimuli for such self‐sustenance. Findings highlight how the enhanced coupling of two biological switches in cancer cells is critical for multiscale feedback control to achieve secretion‐coupled autonomy of growth factors. Synopsis: A combined computational modeling and experimental approach is used to dissect a Golgi‐localized GTPase circuitry in eukaryotes and to understand how it empowers cancer cells to achieve self‐sufficiency in growth factor signaling. Coupling of two classes of GTPases enables closed‐loop feedback and mutual control. Coupling generates dose‐response alignment behavior of sensing and secretion of growth factors. Coupling is critical for multiscale feedback control to achieve secretion‐coupled autonomy. Abstract : A combined computational modeling and experimental approach is used to dissect a Golgi‐localized GTPase circuitry in eukaryotes and to understand how it empowers cancer cells to achieve self‐sufficiency in growth factor signaling.